2016
DOI: 10.1007/s13361-016-1376-2
|View full text |Cite
|
Sign up to set email alerts
|

Dipole Excitation: A New Method for Mass Analysis with a Quadrupole Mass Filter

Abstract: Abstract. Trajectory calculations are used to investigate peak shapes and ion transmission with a proposed new method of mass analysis with a quadrupole mass filter. Dipole excitation is applied to either the x or the y electrodes, or both, to create bands of instability within the first stability region. With excitation between the y electrodes (near β y = 0), ions are removed from the low mass side of a peak, and with ion excitation in x (near β x = 1), ions are removed from the high mass side. The mass reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…5,15 Dipole resonant excitation on small frequencies leads to the appearance of instability bands on the (a, q) stability diagram along iso-b lines. [16][17][18] With linear quadrupoles, an instability band along x ¼ const line is formed when a small dipole rf auxiliary voltage is applied between the X pair of electrodes and y ¼ const with dipole excitation between the Y rods. These instability bands together with the general stability diagram allow the QMF transmission to be increased for the same resolution value.…”
Section: Direct Current Excitation In Y Directionmentioning
confidence: 99%
“…5,15 Dipole resonant excitation on small frequencies leads to the appearance of instability bands on the (a, q) stability diagram along iso-b lines. [16][17][18] With linear quadrupoles, an instability band along x ¼ const line is formed when a small dipole rf auxiliary voltage is applied between the X pair of electrodes and y ¼ const with dipole excitation between the Y rods. These instability bands together with the general stability diagram allow the QMF transmission to be increased for the same resolution value.…”
Section: Direct Current Excitation In Y Directionmentioning
confidence: 99%
“…The early works were devoted mainly to DC dipole excitation in QMF. 810 It was found that the most effective resonant dipole excitation is along the β y line near the boundary β y = 0. 8 This effect occurs due to the low frequency oscillations in the y direction at the stability boundary for the fundamental frequency β Ω / 2.…”
Section: Introductionmentioning
confidence: 99%
“…810 It was found that the most effective resonant dipole excitation is along the β y line near the boundary β y = 0. 8 This effect occurs due to the low frequency oscillations in the y direction at the stability boundary for the fundamental frequency β Ω / 2. For example, if β y = 0.01, then ω y = Ω / 200.…”
Section: Introductionmentioning
confidence: 99%
“…Resonant excitation of ions in a three‐dimensional ion trap was first described by Fisher . Dipole resonant excitation leads to the appearance of instability bands in the ( a , q ) stability diagram along the iso‐ β lines of the characteristic exponents β x , β y or β z . With linear quadrupoles an instability band along β x = const is formed when a small dipole rf auxiliary voltage is applied between the x pair of electrodes and β y = const with dipole excitation between the y rods.…”
Section: Introductionmentioning
confidence: 99%